THERE ARE SOME THINGS MONEYS CAN’T BUY HOW BRAND GESTALT ORCHESTRATES BALI’S BRAND EQUITY - Pongoh, Helena M.; Mandagi, Deske W. (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
The primary focus of this study is to analyze how brand gestalt affects the brand equity of Bali as a destination for tourism. Previous research has not delved deeply into this area, leaving a gap in both practical and theoretical understanding. Therefore, this study seeks to address this gap by establishing a stronger link between various aspects of brand gestalt and brand equity. Data from 305 individuals who had visited Bali, Indonesia, was collected to validate the dimensions of the brand gestalt scale. Using a Structural Equation Model (SEM) analysis with the smartPLS statistical program, the proposed model was tested. The results indicated that not all dimensions of brand gestalt (story, sensescape, servicescape, and stakeholder) have a positive and significant impact on components of brand equity such as perceived quality, brand awareness, brand image, brand associations, and brand loyalty. While servicescape does show significant influences on all component of brand equity, the story dimension only has a significant impact on brand associations and brand loyalty, in contrast to stakeholder dimension, which does not significantly affect these components.